Low‐Dimensional Conduction Mechanisms in Highly Conductive and Transparent Conjugated Polymers. (14th July 2015) - Ugur, Asli; Katmis, Ferhat; Li, Mingda; Wu, Lijun; Zhu, Yimei; Varanasi, Kripa K.; Gleason, Karen K.
<x xml:space="preserve">Abstract</x> Electronic conduction in conjugated polymers is of emerging technological interest for high‐performance optoelectronic and thermoelectric devices. A completely new aspect and understanding of the conduction mechanism on conducting polymers is introduced, allowing the applicability of materials to be optimized. The charge‐transport mechanism is explained by direct experimental evidence with a very well supported theoretical model.